HUBUNGAN BRAND AWARENESS DAN BRAND ASSOCIATION DENGAN MINAT BERTRANSAKSI ULANG DI TOKOPEDIA - Aldedinda Auliantio; Djoko Setyabudi (Interaksi Online, 2023)
This study aims to determine the correlation between Brand Awareness, Brand Association, and Repurchase Intention in Tokopedia as an Online Shopping Transaction Platform. This research used Heuristic-Systematic Model and Self Congruity Theory. This study used a sample of 120 people who had been using Tokopedia atleast in the past last month. This sample data retrieval technique used nonprobability sampling with accidental techniques and Kendall's Tau B analysis. There are two Results of this research; (1) There is a very significant correlation between Brand Awareness and Repurchase Intention in Tokopedia with a significance value of 0.004. The correlation coefficient is 0.338, which means it has a moderate and positive level of correlation. (2) There is also a very significant correlation between Brand Association and Repurchase Intention in Tokopedia with a significance value of 0.006. Meanwhile, the correlation coefficient is 0.325, which means it has a moderate and positive level of correlation.